A hungarista emigráció és 1956 - Tóth Tibor (II. Rákóczi Ferenc Kárpátaljai Magyar Főiskola-"RIK-U" Kft., 2020)
A hungarista mozgalom története nem ért véget Szálasi rendszerének bukásával. Az 1945–56 közötti magyar politikai emigráció rendkívül sokszínű volt társadalmi összetételében, de politikai programjaiban, az emigráció motivációiban is. Ennek képezte részét a hungarista emigráció. Az emigráció mindennapjaiban, politikai kommunikációjában meghatározó szerepe volt a sajtónak. Ez alapján elemzi a tanulmány a hungarista emigráció tudósítását, állásfoglalását 1956-ról. A cikkek jól mutatják, hogy a hungarista emigráció mennyire elszakadt a magyarországi események hátterének és jellegének valósághű megítélésétől.

Abstract. The history of the Hungarist Movement did not end up with the fall of the Szálasi-regime. The Hungarian political emigration between 1945-1956 was extraordinarily versatile not only in its social composition but also in its political programs and in the motivation of the emigration. The Hungarist emigration was a part of it. The Press had a highly significant role in the everyday life of the emigration and in its political communication. It provides the analysis of the report and the views of the Hungarist emigration about 1956 in the study. The articles precisely show to what extent the Hungarist emigration irrealed from the objective, real-life approach of the background and the nature of the Hungarian affairs.

Резюме. Історія гунгаристського руху не закінчилася падінням режиму Салаші. Угорська політична еміграція 1945-56 років була надзвичайно строкатою як з точки зору соціального походження, так і своїми програмами та причинами еміграції. Її частиною була й гунгаристська еміграція. Визначальну роль у житті емігрантів, їхній політичній комунікації відігравала преса. У статті проаналізовано публікації та позицію представників гунгаристської еміграції стосовно подій 1956 року. Тогочасні статті засвідчують, наскільки кореспонденти гунгаристської еміграції були далекими від реальних причин подій в Угорщині та від їх об’єктивної оцінки.
The Hungarist Emigration and 1956
Еміграція гунгаристів і 1956
https://kmf.uz.ua/wp-content/uploads/2021/10/limes-2020-issue-vii_volume-1.pdf
https://opac3.brff.monguz.hu:443/hu/record/-/record/bibBRF00008905
Keywords: magyar politikai emigráció; hungarista mozgalom; emigráns sajtó; 1956; 1956 nyugati megítélése